“Desarrollo de un sistema web aplicando prácticas ágiles para la administración de la clínica dental Dent House” - Grefa Vegay, Carlos Eduardo (2023)
In the following degree work, it was developed at the "Dent House Dental Clinic" located in the city of Latacunga, which was based on the development of a computer system for the administration of the clinic, such as dental medical records and the management of an odontogram for monitoring the treatment of each patient. In the same way, it was necessary to study the current operation of the clinic in order to point out the problems it has in terms of the processes carried out by the dental clinic, for which an interview was conducted to obtain the system requirements based on said problems. and thus design an effective architecture that manages to comply with all the established requirements.